Congenital ocular motor apraxia - Carrasquinho, S (2012)
PURPOSE: Congenital ocular motor apraxia is a rare disease characterized by defective or absent voluntary and optically induced horizontal saccadic movements. Jerky head movements or thrusts on attempted lateral gaze are a compensatory sign. Most affected children have delayed motor and speech development. Cases associated with systemic diseases, neurologic maldevelopment, metabolic deficits, and chromosomal abnormalities have been described. METHODS: Case report and review of the scientific literature. RESULTS: The authors describe the ophthalmologic, pediatric, and neurologic evaluations and follow up of a child with impaired horizontal saccades, jerky head movements, and delayed motor and speech development. CONCLUSIONS: Congenital ocular motor apraxia is an uncommon disorder of ocular motility. Even so, ophthalmologists should be aware of the developmental delay and the other associated conditions, in order to grant the patients the multidisciplinary assistance they often require.